(untitled) (KYAMC Journal, 2019)
Background: Recent studies suggest that surgical diathermy shows better clinical outcome in the context of incision time, wound related postoperative pain, postoperative wound infections, and length of postoperative hospital stay and cosmetic outcome of scar in cases of elective surgical patients. Objectives: Compare the efficacy and safety of surgical diathermy versus conventional surgical blade for making skin incisions in elective mid-line laparotomy and to evaluate weather cutting diathermy is an effective and better alternative to surgical blade incision. Materials and Methods: This prospective study was carried out in the department of surgery at BSMMU, Dhaka over a period of one year. Sample size was 64 with a follow up duration for 6 month. In Group I (D), skin incision was taken with diathermy, and in Group II (S), incision was taken with surgical blade. Results: Compared with a scalpel incision, cutting diathermy resulted in significantly shorter incision times and reduced post-operative wound related pain (P = <0·001), shorter duration of postoperative hospital stay (P = 0.003) with no differences in the wound complication rate and cosmetic outcome of scar. Conclusions: The study has demonstrated that surgical cutting diathermy is a safe and effective method to make skin incisions in elective surgery KYAMC Journal Vol. 10, No.-3, October 2019, Page 143-146